2019
DOI: 10.1103/physrevd.99.115011
|View full text |Cite
|
Sign up to set email alerts
|

Probing nonstandard lepton number violating interactions in neutrino oscillations

Abstract: We discuss lepton number violating processes in the context of long-baseline neutrino oscillations. We summarise and compare neutrino flavour oscillations in quantum mechanics and quantum field theory, both for standard oscillations and for those that violate lepton number. When the active neutrinos are Majorana in nature, the required helicity reversal gives a strong suppression by the neutrino mass over the energy, (m ν /E ν ) 2 . Instead, the presence of non-standard lepton number violating interactions inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 163 publications
(182 reference statements)
0
21
0
Order By: Relevance
“…In the Majorana case, there are also lepton number violating operators such as (ν c e)(d R u L ), which, however, can not be generated by dimension-six operators[5].…”
mentioning
confidence: 99%
“…In the Majorana case, there are also lepton number violating operators such as (ν c e)(d R u L ), which, however, can not be generated by dimension-six operators[5].…”
mentioning
confidence: 99%
“…Finally, some NSI models may address current experimental anomalies, and/or predict non-trivial experimental signatures like neutrino tridents (Secs. 8,18,24). It was shown that dedicated searches for certain scenarios involving BSM in the neutrino sector or light dark matter in neutrino experiments can be quite powerful (Secs.…”
Section: Outlook and Discussion (Machado)mentioning
confidence: 99%
“…Refs. [22,23] (source-detector NSI), [24] (lepton-numberviolating NSI), [25] (scalar NSI) and [26] (dark NSI).…”
Section: Introduction To Non-standard Neutrino Interactions (Denton)mentioning
confidence: 99%
“…We note that the above limits are from oscillations conserving total lepton number. While it is in principle possible to observe LNV in oscillations, this requires new physics beyond sterile neutrinos such as right-handed currents [131].…”
Section: Active-sterile Neutrino Oscillationsmentioning
confidence: 99%